Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

Pushout draft #335

Draft
wants to merge 18 commits into
base: master
Choose a base branch
from
Draft
Changes from 1 commit
Commits
File filter

Filter by extension

Filter by extension

Conversations
Failed to load comments.
Loading
Jump to
Jump to file
Failed to load files.
Loading
Diff view
Diff view
73 changes: 73 additions & 0 deletions source/UF/Pushouts.lagda
Original file line number Diff line number Diff line change
Expand Up @@ -127,6 +127,79 @@ inverse-cocone-map f g X u u' =

\end{code}

Now we will define the universal property, induction principle and propositional
computation rules for pushouts and show they are inter-derivable.

\begin{code}

Pushout-Universal-Property
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (X : 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
→ 𝓤 ⊔ 𝓥 ⊔ 𝓦 ⊔ 𝓤' ⊔ 𝓣 ̇
Pushout-Universal-Property S X f g i j G
= (S → X) ≃ cocone f g X
IanRay11 marked this conversation as resolved.
Show resolved Hide resolved

Pushout-Induction-Principle
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (P : S → 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
→ 𝓤 ⊔ 𝓥 ⊔ 𝓦 ⊔ 𝓤' ⊔ 𝓣 ̇
Pushout-Induction-Principle {_} {_} {_} {_} {_} {A} {B} {C} S P f g i j G
= (l : (a : A) → P (i a))
→ (r : (b : B) → P (j b))
→ ((c : C) → transport P (G c) (l (f c)) = r (g c))
→ (x : S) → P x

Pushout-Propositional-Computation-Rule₁
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (P : S → 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
(S-ind : Pushout-Induction-Principle S P f g i j G)
→ 𝓤 ⊔ 𝓥 ⊔ 𝓦 ⊔ 𝓣 ̇
Pushout-Propositional-Computation-Rule₁
{_} {_} {_} {_} {_} {A} {B} {C} S P f g i j G S-ind
= (l : (a : A) → P (i a))
→ (r : (b : B) → P (j b))
→ (H : (c : C) → transport P (G c) (l (f c)) = r (g c))
→ (a : A)
→ S-ind l r H (i a) = l a

Pushout-Propositional-Computation-Rule₂
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (P : S → 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
(S-ind : Pushout-Induction-Principle S P f g i j G)
→ 𝓤 ⊔ 𝓥 ⊔ 𝓦 ⊔ 𝓣 ̇
Pushout-Propositional-Computation-Rule₂
{_} {_} {_} {_} {_} {A} {B} {C} S P f g i j G S-ind
= (l : (a : A) → P (i a))
→ (r : (b : B) → P (j b))
→ (H : (c : C) → transport P (G c) (l (f c)) = r (g c))
→ (b : B)
→ S-ind l r H (j b) = r b

Pushout-Propositional-Computation-Rule₃
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (P : S → 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
(S-ind : Pushout-Induction-Principle S P f g i j G)
(S-comp₁ : Pushout-Propositional-Computation-Rule₁ S P f g i j G S-ind)
(S-comp₂ : Pushout-Propositional-Computation-Rule₂ S P f g i j G S-ind)
→ 𝓤 ⊔ 𝓥 ⊔ 𝓦 ⊔ 𝓣 ̇
Pushout-Propositional-Computation-Rule₃
{_} {_} {_} {_} {_}{A} {B} {C} S P f g i j G S-ind S-comp₁ S-comp₂
= (l : (a : A) → P (i a))
→ (r : (b : B) → P (j b))
→ (H : (c : C) → transport P (G c) (l (f c)) = r (g c))
→ (c : C)
→ apd (S-ind l r H) (G c) ∙ S-comp₂ l r H (g c)
= ap (transport P (G c)) (S-comp₁ l r H (f c)) ∙ H c

Pushout-Universal-Property-implies-Induction
: {A : 𝓤 ̇} {B : 𝓥 ̇} {C : 𝓦 ̇} (S : 𝓤' ̇) (X : 𝓣 ̇) (P : S → 𝓣 ̇)
(f : C → A) (g : C → B) (i : A → S) (j : B → S) (G : i ∘ f ∼ j ∘ g)
→ Pushout-Universal-Property S X f g i j G
→ Pushout-Induction-Principle S P f g i j G
Pushout-Universal-Property-implies-Induction = ?

\end{code}

Now we will use a record type to give the pushout, point and path constructors,
and the induction principle along with propositional computation rules.

Expand Down